ANALISA DAMPAK PENURUNAN INTENSITAS INTERAKSI SOSIAL AKIBAT PENERAPAN PHYSICAL DISTANCING DAN SOCIAL DISTANCING TERHADAP TINGKAT STRES SESEORANG: STUDI KASUS DI SALAH SATU KELAS DI IAIN SULTAN AMAI GORONTALO - Suhendra Iskandar (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
Research has been conducted on the impact of decreasing the intensity of social interaction due to the application of physical distancing and social distancing on a person's stress level. Research was done with semi-quantitative analysis method using pearson product moment formula in which decrease in the number of social interactions as independent variable and stress level as dependent variable. A total of 22 students in a certain class at IAIN Sultan Amai Gorontalo were observed to determine the intensity of their social interactions before and after the implementation of physical distancing and social distancing as well as their stress level during the implementation of physical distancing and social distancing and then looking for correlations. The result show that the correlation between the two variables is 0.7344 and this value is greater than the critical r for n=22, which is 0.537. Thus, it is proven that the decrease in the intensity of social interaction due to the application of physical distancing and social distancing is directly influence a person's stress level in which the bigger the the decrease in the intensity of social interaction, the bigger the stress level.